Animosity. Volume 1. The wake - Bennett, Marguerite (Aftershock Comics, 2017)
"The world is plunged into chaos as the newly-intelligent Animals fight humanity, and each other, for their own lives, liberty, and pursuit of happiness. In the midst of the turmoil is Jesse, an 11-year-old girl, and her dog, Sandor, who is devoted to Jesse and her safety. One year after the incident, Jesse and Sandor begin a cross-country journey to find Jesse's half-brother, Adam, who is living in San Francisco. But the journey there, and what happens when they arrive, was something neither man nor beast was prepared for."--|cProvided by publisher.